2020
DOI: 10.1145/3381014
|View full text |Cite
|
Sign up to set email alerts
|

FluSense

Abstract: We developed a contactless syndromic surveillance platform FluSense that aims to expand the current paradigm of influenza-like illness (ILI) surveillance by capturing crowd-level bio-clinical signals directly related to physical symptoms of ILI from hospital waiting areas in an unobtrusive and privacy-sensitive manner. FluSense consists of a novel edge-computing sensor system, models and data processing pipelines to track crowd behaviors and influenza-related indicators, such as coughs, and to predict daily IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…A portable device, called FluSense [54,58], was developed by the University of Massachusetts Amherst. Figure 5 shows the components of the FluSense machine that was operated by an AI-based neural network that can real-time identify cough and crowd size and directly evaluate and collect data for flu-like diseases, such as COVID-19.…”
Section: Observing Covid-19 Through Ai-based Cough Sound Analysismentioning
confidence: 99%
“…A portable device, called FluSense [54,58], was developed by the University of Massachusetts Amherst. Figure 5 shows the components of the FluSense machine that was operated by an AI-based neural network that can real-time identify cough and crowd size and directly evaluate and collect data for flu-like diseases, such as COVID-19.…”
Section: Observing Covid-19 Through Ai-based Cough Sound Analysismentioning
confidence: 99%
“…In that study, FluSense collected and analyzed 21 million non-speech audio samples and around 350,000 waiting room thermal images. The study (21) showed that FluSense accurately predicted the patient daily counts (Pearson correlation coefficient = 0.95). The FluSense platform did not take into consideration all respiratory illnesses nor additional health data.…”
Section: Related Workmentioning
confidence: 92%
“…FluSense uses a thermal camera, a microphone array and a neural computing engine to characterize cough sound changes of individuals waiting in hospitals in a real-time manner. The researchers conducted a 7-month study in four public waiting areas equipped with FluSense within the hospital of a large university from December 2018 to July 2019 (21). In that study, FluSense collected and analyzed 21 million non-speech audio samples and around 350,000 waiting room thermal images.…”
Section: Related Workmentioning
confidence: 99%
“…Among AI-Health related works, some researchers have tried to predict the sickness trend of specific areas [33], to develop crowd counting and density estimation methodologies in public places [34], or to determine the distance of individuals from the popular swarms [35] using a combination of visual and geo-location cellular information. However, such research works suffer from challenges such as skilled labour or the cost of designing and implementing the infrastructures.…”
Section: Ai-based Researchmentioning
confidence: 99%